Dry Eye among Medical Students of Gandaki Medical College, Pokhara, Nepal - Tuladhar, S; Poudel, B; Shahi, D (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Dry eye disease results from decreased tear production, increased evaporation of tears and inflammation. Medical students often have dry eyes due to use of projectors, computers for study and also due to use of mobiles. Objective: The present study was undertaken to find out dry eye by Schirmer 1 test with local anesthesia and measurement of wetting of Schirmer test strip. Methods: Schirmer 1 test with anesthesia was performed on 200 medical students from June 1, 2017 to June 1, 2018 after obtaining informed consent and after applying some exclusion criteria. The test was performed by first applying 4% topical lignocaine and then using Whatman filter paper no 41 and wetting of the filter paper measured after five minutes and time noted. Results: 146 (73%) Among 200 Students, were males and 54 (27%) were females. Mean age of patients was 21.73 ±1.42 years. Mild dry eye was seen in 19.5%, moderate in 13% and severe dry eye in 13.5% of medical students Conclusion: Dry eye is one of common ocular disease among medical students.